"Eye Dropping"—A Case Report of Transconjunctival Lysergic Acid Diethylamide Drug Abuse. Issue 10 (October 2018) - Lo, Danielle; Cobbs, Lucy; Chua, Michael; Young, Joshua; Haberman, Ilyse D.; Modi, Yasha
Abstract : Purpose: To report a case of bilateral toxic corneal and conjunctival epitheliopathy secondary to administration of filter paper impregnated with lysergic acid diethylamide (LSD) in the inferior conjunctival fornices. Methods: This is a single case report of an 18-year-old man who presented to the emergency department with acute, bilateral eye pain and redness of 24 hours. The patient admitted to placing folded strips of blotting paper impregnated with LSD into the inferior fornices of his eyes the previous night. Results: The patient was found to have localized bilateral corneal and conjunctival abrasions with underlying subconjunctival hemorrhage. Conjunctival abrasion was "kissing, " involving the bulbar and palpebral conjunctiva, corresponding to the presumed location of the filter paper. There was no corneal stromal opacification. He was lost to follow up within 1 week of initial presentation but stated that his symptoms improved. Conclusions: To the best of our knowledge, this is the first reported case of bilateral hemorrhagic conjunctival abrasion and corneal abrasion secondary to LSD. "Kissing" conjunctival lesions, which have been previously reported with heroin use, should raise suspicion for drug abuse.